2016
DOI: 10.1177/0301006616659073
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the Haptic Perception of Material Properties

Abstract: The ability of 26 younger (mean age was 22.5 years) and older adults (mean age was 72.6 years) to haptically perceive material properties was evaluated. The participants manually explored (for 5 seconds) 42 surfaces twice and placed each of these 84 experimental stimuli into one of seven categories: paper, plastic, metal, wood, stone, fabric, and fur/leather. In general, the participants were best able to identify fur/leather and wood materials; in contrast, recognition performance was worst for stone and pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The experimental results show that young and old groups have significant differences in the performance of angle sorting tasks, as shown in Figure 12. Moreover, compared with the younger group, the performance of the elderly group has experienced a significant decline [t 22.79 = −2.784, p = 0.011, Cohen's d = −1.166], which is consistent with previous research showing that the ability to discern the angle decreases with age [44,45]. It is well known and confirmed that since cognitive ability declines with age, the angle discrimination ability of elderly subjects is significantly weaker than that of younger participants [46][47][48].…”
Section: Resultssupporting
confidence: 86%
“…The experimental results show that young and old groups have significant differences in the performance of angle sorting tasks, as shown in Figure 12. Moreover, compared with the younger group, the performance of the elderly group has experienced a significant decline [t 22.79 = −2.784, p = 0.011, Cohen's d = −1.166], which is consistent with previous research showing that the ability to discern the angle decreases with age [44,45]. It is well known and confirmed that since cognitive ability declines with age, the angle discrimination ability of elderly subjects is significantly weaker than that of younger participants [46][47][48].…”
Section: Resultssupporting
confidence: 86%
“…It is thus abundantly clear that dynamic touch on fine textures exhibits an age-related decline in discrimination ability which may well be related to the decrease in tactile discrimination sensitivity with age reported for static touch 1 4 and object discrimination 3 , 36 . The physical dimensions underpinning the active touch discrimination of fine textures have previously been identified 10 as being associated with the friction coefficient (and the resulting finger loading 15 ), and the wavelength of the surfaces.…”
Section: Resultsmentioning
confidence: 97%
“…Discriminative aspects of tactile function are known to decline with age, including the ability to detect light touch (Newman, 1979;Bruce, 1980;Bruce and Sinclair, 1980;Thornbury and Mistretta, 1981), or vibration at different frequencies (Kenshalo, 1986;Thomson et al, 1993;Gescheider et al, 1994;Goble et al, 1996), to discriminate between different levels of surface roughness (Norman et al, 2016), or the distance between spatial features (Stevens, 1992;Stevens and Patterson, 1995;Stevens and Choo, 1996;Stevens et al, 1998;Desrosiers et al, 1999;Dinse et al, 2006), or to discriminate the direction of movement (Olausson et al, 1997;Lundblad et al, 2020). These capacities decline after around 60 years of age and this may be due to changing properties of the skin as well as neural degeneration of the peripheral and central nervous systems (Wickremaratchi and Llewelyn, 2006;Skedung et al, 2018).…”
Section: Changes In Touch Perceptionmentioning
confidence: 99%